Hospital Service Quality and Quality Achievement in Revisit Intention: A Systematic Literature Review - Ramadhan, Variansa Sava; Ichsan, Burhanuddin; Jatmiko, Safari Wahyu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Background: Hospital service quality and achievement of quality standards are important factors that determine patient repeat visit intention. Patients tend to choose healthcare facilities that can provide a positive, safe, and quality experience. This article aims to review the relationship between service quality, hospital quality achievement, and patient revisit intention through a literature review.Method: This study uses a systematic literature review method by examining scientific articles from the PubMed, Scopus, and Google Scholar databases in the period 2020–2024. Keywords used include "healthcare quality", "hospital service quality", "patient satisfaction", "revisit intention", and "quality achievement".Results: The systematic literature review shows a positive relationship between service quality, quality achievement, and revisit intention. The main influencing factors are the SERVQUAL dimension (tangible, reliability, responsiveness, assurance, and empathy), hospital accreditation, and the implementation of patient safety standards.Conclusion: Service quality and quality achievement are proven to have a significant contribution to repeat visit intention. Hospitals need to improve their quality management system and service quality continuously to maintain patient loyalty.